Environmental Learning based on Higher Order Thinking Skills: A Needs Assessment - Ichsan, Ilmi Zajuli; Sigit, Diana Vivanti; Miarsyah, Mieke (International Journal for Educational and Vocational Studies, 2019)
Environmental learning at the school and university levels, often still uses conventional learning. This is a problem, considering the ability of students' Higher Order Thinking Skills (HOTS) is very necessary for the 21st century. The purpose of this study is to do need assessment on learning media, teaching materials, learning materials, worksheets, and learning evaluations used in the learning environment in schools and universities. The study was conducted from November 2017 - January 2019 at several schools in Bekasi and one university in Jakarta. The research method used is descriptive method with data collection techniques using observation and interviews. The results showed that media learning, teaching materials, learning materials, students worksheets, and learning evaluations at various levels were not all based on HOTS. HOTS-based learning has been applied at the university level and senior high school but is still rarely used. This is due to the lack of development in environmental learning. The conclusion of this study is that environmental learning is not all HOTS-based.